2014
DOI: 10.1186/1471-2164-15-24
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome profiling of granulosa cells of bovine ovarian follicles during growth from small to large antral sizes

Abstract: BackgroundAt later stages of folliculogenesis, the mammalian ovarian follicle contains layers of epithelial granulosa cells surrounding an antral cavity. During follicle development granulosa cells replicate, secrete hormones and support the growth of the oocyte. In cattle, the follicle needs to grow > 10 mm in diameter to allow an oocyte to ovulate, following which the granulosa cells cease dividing and differentiate into the specialised cells of the corpus luteum. To better understand the molecular basis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
88
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(103 citation statements)
references
References 90 publications
(103 reference statements)
13
88
1
1
Order By: Relevance
“…Real-time PCR data revealed that the expression of Timp1 mRNA had a significant increase in its expression levels with increasing follicular size and higher level in corpus luteum. Similar finding has been reported that the expression of Timp1 mRNA in the GCs of bovine antral follicles were significantly higher in large follicles than that in small follicles [37]. Therefore, we guess that the increasing expression of Timp1 during the process of follicle growth may be crucial for ovarian follicle development and ovulation.…”
Section: Discussionsupporting
confidence: 85%
“…Real-time PCR data revealed that the expression of Timp1 mRNA had a significant increase in its expression levels with increasing follicular size and higher level in corpus luteum. Similar finding has been reported that the expression of Timp1 mRNA in the GCs of bovine antral follicles were significantly higher in large follicles than that in small follicles [37]. Therefore, we guess that the increasing expression of Timp1 during the process of follicle growth may be crucial for ovarian follicle development and ovulation.…”
Section: Discussionsupporting
confidence: 85%
“…It is likely that the extracted ovine stromal tissue in this study contained microscopic follicles. Our finding that temporal gene expression in stroma is not synchronized by LH as previously reported in rodent whole ovaries [22] can be explained by the fact that microscopic follicles likely do not possess receptors for LH [32,33]. This is supported by the finding that LH receptor mRNA only appears after antral formation in bovine follicles [34].…”
Section: Discussionsupporting
confidence: 59%
“…To understand the molecular basis of follicular growth and GC maturation, Hatzirodos et al (2014) undertook transcriptome profiling of GCs from small and large healthy bovine follicles. Substantial changes in gene expression were observed in GCs as follicles enlarged from small to large antral sizes.…”
Section: Pi3k/pten/akt and Tsc/mtor Pathways And Ovarian Somatic Cellsmentioning
confidence: 99%